2023
DOI: 10.3390/vaccines11050989
|View full text |Cite
|
Sign up to set email alerts
|

BNT162b2 COVID-19 Vaccines in Children, Adolescents and Young Adults with Cancer—A 1-Year Follow-Up

Abstract: (1) Background: Children and young adults with cancer are poorly represented in COVID-19 vaccination studies, and long-term protection conferred by vaccination is not known. (2) Objectives: 1. To determine the adverse effects associated with BNT162B2 vaccination in children and young adults with cancer. 2. To assess its efficacy in stimulating immunological response and in preventing severe COVID-19 disease. (3) Methods: Retrospective single-center study evaluating patients aged 8 to 22 years, with cancer, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Our results are novel, as data on immune responses to SARS-CoV-2 vaccinations in pediatric immunocompromised patients are scarce, in particular, regarding data on long-term follow-up [ 5 7 ]. Corroborating our results reported previously [ 6 ], one retrospective study reported on good efficacy of SARS-CoV-2 vaccination in 13 patients (median age 17 years) receiving chemotherapy for a solid tumor [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results are novel, as data on immune responses to SARS-CoV-2 vaccinations in pediatric immunocompromised patients are scarce, in particular, regarding data on long-term follow-up [ 5 7 ]. Corroborating our results reported previously [ 6 ], one retrospective study reported on good efficacy of SARS-CoV-2 vaccination in 13 patients (median age 17 years) receiving chemotherapy for a solid tumor [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Corroborating our results reported previously [ 6 ], one retrospective study reported on good efficacy of SARS-CoV-2 vaccination in 13 patients (median age 17 years) receiving chemotherapy for a solid tumor [ 7 ]. Donze et al [ 5 ] evaluated the anti-SARS-CoV-2 immunity in 38 pediatric cancer patients and assessed the humoral, but not the cellular immune response. At 259 days post-vaccination, the probability of maintaining immunity against SARS-CoV-2 declined to 50% in the 15/38 patients who acquired post-vaccination immunity during the first 3 months after vaccination [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations